Impact of multicentre diagnostic workup in patients with pancreatic cancer on repeated diagnostic investigations, time-to-diagnosis and time-to-treatment: A nationwide analysis. Issue 10 (October 2022) - Hopstaken, Jana S.; Vissers, Pauline A.J.; Quispel, Rutger; de Vos-Geelen, Judith; Brosens, Lodewijk A.A.; de Hingh, Ignace H.J.T.; van der Geest, Lydia G.; Besselink, Marc G.; van Laarhoven, Kees J.H.M.; Stommel, Martijn W.J.
Abstract: Background: Due to the centralization of pancreatic surgery, patients with suspected pancreatic cancer may undergo diagnostic workup in both a non-pancreatic centre and a pancreatic centre, i.e. multicentre workup. This retrospective study assessed whether multicentre diagnostic workup is associated with repeated diagnostics, delayed time-to-diagnosis, delayed time-to-treatment, survival and whether variation existed among pancreatic cancer networks. Methods: This nationwide study included all patients diagnosed with non-metastatic pancreatic ductal adenocarcinoma (PDAC) in 2015, registered by the Netherlands Cancer Registry. A delayed time-to-diagnosis was defined as ≥3 weeks from initial hospital visit to final diagnosis. A delayed time-to-treatment was defined as ≥6 weeks from the first hospital visit to start of first tumour treatment. Multilevel logistic regression analyses and survival analyses were performed. Results: In total, 931 patients with non-metastatic PDAC were included. Overall, 175 patients (19%) underwent a multicentre diagnostic workup, which was significantly associated with repeated diagnostic investigations (OR = 6.31, 95% CI 4.13–9.64, P < 0.0001), a delayed time-to-diagnosis (OR = 2.66 95% CI 1.74–4.06, P < 0.001), and a delayed time-to-treatment (OR = 1.93 95% CI 1.12–3.31, P = 0.02), but not with decreased survival (HR = 1.09 95% CI 0.83–1.44; P = 0.532). Variation in outcomes per network was observed, especially for time-to-treatment, though the ICC was not statistically significant (P = 0.065). Conclusion: Multicentre diagnostic workup for patients with PDAC is associated with repeated diagnostic investigations, a delayed time-to-diagnosis and delayed time-to-treatment compared to patients with monocentre workup. To reduce costs and improve treatment times, efforts should be made to improve network coordination, for example via network care pathways.